PENERAPAN COST REDUCTION STRATEGIES DI MASA PANDEMI COVID-19 PADA USAHA KECIL MENENGAH (UMKM) KOTA BOGOR (Studi pada Anggota UMKM di Komunitas Kefir Bogor) - Sri Hastuti (JURNAL LENTERA BISNIS, 2021)
This research purpose to know the application of Cost Reduction Strategies on Micro Small and Medium Enterprises (MSME). Cost reduction strategies have the meaning of "change" even though it is better known as "cost reduction" but any company that dares to implement cost reduction means that it is ready to change.  The problem in the application of Cost Reduction Strategies is the difficulty in making a priority scale to determine cost items that can be streamlined and not optimal in carrying out the cost reduction stage. The focus of this study is more on the application of business process change strategies and also the efficiency of human resources. This research uses a qualitative description method. The technique of collecting data was done by interviewing and surveying a number of respondents using a sampling technique. The survey results showed 67% applied the concept of efficiency in business processes and 25% implemented a human resource efficiency strategy (streamlining), 8% of respondents stated that they did not implement an efficiency strategy during a pandemic because their income has actually increased. From the survey results, it shows that the main focus of MSME entrepreneurs when there is a decline in turnover is to make improvements to the production process firsts, streamlining is the final choice.Key words: Cost Reduction Strategies, UMKM Bogor, Covid-19